Distinct modulation of interhemispheric inhibitory mechanisms during movement preparation reveals the influence of cognition on action control. (February 2018) - Hinder, Mark R.; Puri, Rohan; Kemp, Sarah; Waitzer, Sara; Reissig, Paola; Stöckel, Tino; Fujiyama, Hakuei
Abstract: When selecting actions based on visual warning stimuli (WS), corticospinal excitability (CSE) is initially suppressed, consistent with a neural mechanism to prevent premature release of the competing responses. Despite being implicated in between-hand movement selection and preparation, the role that interhemispheric inhibition (IHI) may play in this 'impulse control' mechanism is not known. Participants performed a warned, between-hand, choice reaction time (RT) task in which the informativeness of the WS (with regards to which hand would be required to respond) was manipulated. Transcranial magnetic stimulation (TMS) assessed CSE of the right primary motor cortex (M1) and IHI from left to right M1 with 10 (IHI10) and 40 (IHI40) msec interstimulus intervals during movement selection and preparation. Consistent with impulse control, CSE was initially suppressed prior to both left and right hand actions, irrespective of WS informativeness. Subsequent CSE increases occurred in the responding hand which were larger, and occurred earlier, following an informative WS. Importantly, these increases strongly predicted response times. In contrast to the generic CSE suppression, an informative WS permitted a hand-specific release of IHI10 in the responding hand, whereas IHI40 was released in both hands. As releases of IHI cannot explain a simultaneous suppression of CSE, this suggests several distinct movement preparation mechanisms are at play with IHI modulation occurring independently from impulse control. Notably, the findings support the notion that IHI10 and IHI40 between contralateral motor regions are mediated by discrete transcallosal pathways, and are differently modulated by specific motor and cognitive attributes of a rapid choice task.